STUDIES ON EFFECT OF SOURCES OF SILICA ON RICE CROP IN SALINE SOIL OF BHAVANAMVARIPALEM VILLAGE - K. ANNY MRUDHULA *; Y. RADHA KRISHNA (The Journal of Research ANGRAU, 2020)
Rice crop is susceptible to salinity and its yield is severely limited under salt stress environment. However, one favourable character of rice is that it is a silicate accumulator crop.It means Si increased cellwall binding of Na+ in the root, while decreasing its transport to the shoot. Different source of silica on rice crop at farmer’s field in saline soil was studied. The experiment was laid out in randomized block design with four silicate sources as treatments and replicated four times. Four silicate sources viz., potassium silicate, calcium silicate, paddy straw and paddy husk were evaluated for yield and yield components against control (without silica). Among different sources of silica, potassium silicate treatment recorded significantly higher grain yield (5686 kg ha-1)when compared to no silica treatment (4631 kg ha-1). Higher potassium uptake of rice was observed in potassium silicate application treatment followed by calcium silicate application. Lower sodium uptake in rice was recorded in potassium silicate application treatment and it was on par with calcium silicate application treatment which was significantly superior to other treatments.